ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA PEKANBARU TAHUN 2021 -2023 - Ahmad Rahbani Sulaiman S; Dian Indah Hayati; Afriosa Syawitri (Universitas Negeri Padang, 2024)
This study analyzes the effectiveness and contribution of hotel and restaurant tax revenues to the Regional Original Revenue (Pendapatan Asli Daerah, PAD) of Pekanbaru City from 2021 to 2023. Using a quantitative approach, the research relies on secondary data from the financial reports of the Pekanbaru City Government. The findings reveal that the effectiveness of hotel and restaurant taxes is categorized as very effective, with an average effectiveness of 94% and 106%, respectively. However, the contribution of these taxes to total PAD is relatively low, averaging 5% for hotel taxes (categorized as very low) and 14% for restaurant taxes (categorized as low). These results suggest a need to optimize the potential of these sectors through strategies such as increasing tax awareness, promoting tourism, and leveraging technology. The study recommends diversifying PAD sources and fostering collaborative partnerships with business operators to support sustainable development in Pekanbaru City.. Keywords: Regional Original Revenue, Hotel Tax, Restaurant Tax